Tigecycline: pharmacological concerns and resistance - Paudel, Rama; Nepal, Hari P. (International Journal of Basic & Clinical Pharmacology, 2020)
Tigecycline, a semisynthetic derivative of minocycline, has a broad spectrum of activity against both gram positive and gram negative multidrug resistant bacteria. The drug acts on 30S ribosomal subunit and inhibits protein synthesis. Since the drug has excellent tissue distribution, it is very useful for treatment of skin infections, intra-abdominal infections and pneumonia. Side effects of the drug are usually mild. The common side effects include nausea and vomiting. The exact mechanism of resistance remains unclear. However, resistance mediated by enhanced expression of resistance nodulation cell division (RND) type efflux pumps is one of the most frequently reported mechanisms. Resistance has been observed worldwide. However, the rate of resistance is low.